(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To examine the associations between stress, job control, and clinical teaching self-efficacy among nursing clinical instructors. Methods: A descriptive study was conducted on 400 nursing visiting lecturers at Nam Dinh University of Nursing. Data were collected via Google Forms using the self-efficacy in teaching tool - nursing education, the perceived stress scale, and the job content questionnaire. Results: Most lecturers reported moderate-to-high levels of self-efficacy, stress, and job control, with rates of 63%, 87.5%, and 95.3%, respectively. The proportion of moderate-to-high self-efficacy in the low-stress group (84%) was significantly higher than in the other groups (p < 0.05). Similarly, a higher rate of moderate-to-high self-efficacy was observed among those with high job control (71.9%, p < 0.05). Multivariable logistic regression analysis indicated that age, work seniority, healthcare tier, and job control were significant factors associated with the clinical teaching self-efficacy of nursing instructors. Conclusion: Stress levels significantly impact clinical teaching self-efficacy, while job control is positively associated with self-efficacy among nursing instructors.